(3MGTjI HGdi RGOg Ydi TQM SYOi CafOi Ydi GdbGVi GdHjVGhis - (3eUWai Hf SdjeGf HGdi RGOgs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3SHMGf ef CfRd Ydi YHOg cJGHkG ajg BjGJ HjfGJ , hUdi Gddg JYGdi Ydi QShdg GdeDjO HGdeYLRGJ GdHGgQGJ , GdPi EfbWY Hg GdhMi s
(3BNQgG (B:s
(3hGdOdGdI Ydi GdJYOi hYOe GdJYOi djSJ ai GdBjI heYfi GdCRhGL aEf cdGgeG ef Gdg dgeG Ef NjQ aNjQ hEf TQ aTQ , adG hLg ddeTGcdI bhdg (B( (3hdjLYdhgG (B) (3Edi BNQg aCQjO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs